Relações etnicorraciais na educação profissional: currículo e práticas pedagógicas - Moura, Ana Carolina de Paula (2021)
This dissertation has as focus the professional apprenticeship program, having as reference the Law 10.097/00, which deliberates on the insertion of young people in the labor market, in the dimensions of its promotion in relation to the development of educational practices in this teaching modality. The object of study is based on the design of curriculum and professional learning practices in the anti-racist perspective, that is defined by the opinion or feeling of opposition to racism. In this sense, we take as a basis Law 10.639/03, which predicts the mandatory teaching of Afro-Brazilian history and culture in both Elementary and High School. A research aims to analyze a representation of black people in books and teaching resources used in vocational education, considering the conceptions of an anti-racist education. The qualitative approach research has as methodological procedure the document analysis, having in view the classification of images and specific contents that embraces black subjects, as well as the perspective of combating racism, expressed in the contents of handouts, physical and digital educational materials and pedagogical practices of training courses. The theoretical foundations are supported by authors such as Abdias Nascimento (2016); Paulo Freire (1996); Ana Célia da Silva (2011); Branca Jurema Ponce (2019); Circe Maria Fernandes Bittencourt (1993); Sueli Carneiro (2011); Maria Aparecida Silva Bento (2002); Miguel G. Arroyo (2013) e Jacques Delors (1998). References also include documents as: Manual da Aprendizagem (2006); Law 10.639/03 and the Law 10.097/00. The analyzes specifically include reflections on the effectiveness of professionalizing education in addressing about cross-cutting themes given its significance for the young apprentice's integral learning, besides characterizing themes and contents inserted in educational practices in relation to the ethnic-racial issues in the professional education. The investigative results make explicit relations between education, social inequality and racial relations, exposing evidences of racism and anti-racism